THE EFFECTIVENESS OF THERAPEUTIC EXERCISE PROGRAMS IN IMPROVING CARDIOVASCULAR FITNESS IN INDIVIDUALS WITH CARDIOVASCULAR DISEASES - Mahdi Ali Mahdi Alqahtani, Rami Saud Abdulhadi Althobaiti, Fahad Mohsenmofhedalshamari, Amro Ahmed Mahdi, Abdulelahgasemhadihamali, Ahmad Humidanalqusir, Ali Abdulrahman Aldakhil, Mohammed Abdullah Alowaid, Ali Hussain Alnowiser,; Abdulrahman Zahi F Alruwaili, Abdullah Mohamed Abdullah Alhafaf, Mohammed Abdulrahman Aljahidly, Hamad Nasser Mubarkalshadied, (Chelonian Research Foundation, 2022)
Engaging in regular physical activity that involves utilizing large muscle groups, such as walking, jogging, or swimming, leads to cardiovascular adaptations that enhance exercise capacity, endurance, and skeletal muscular strength. Regular physical exercise also serves as a preventive measure against the development of coronary artery disease (CAD) and alleviates symptoms in those already diagnosed with cardiovascular disease. Additionally, there is evidence indicating that exercise can lower the likelihood of developing various chronic illnesses, such as type 2 diabetes, osteoporosis, obesity, depression, and breast and colon cancer. It also offers recommendations for healthcare professionals on how to implement physical activity programs for their patients and highlights areas that require further research. This statement primarily emphasizes aerobic physical activity and does not explicitly assess resistance activities, such as weight lifting. This is because the majority of studies investigating the relationship between physical activity and cardiovascular disease have mostly examined aerobic activity. The writing group has consistently used summary papers or meta-analyses to substantiate its results and suggestions wherever feasible. This research corroborates the advice given by the Centers for Disease Control and Prevention (CDC) and the American College of Sports Medicine (ACSM) that persons should participate in at least 30 minutes of physical exercise at a moderate level or higher on most, if not all, days of the week Keywords: physical activity, cardiovascular disease, therapeutic exercise, type 2 diabetes, review.